Comparing the mood of physical education students: effect of two teaching models - Pérez-Muñoz, Salvador; Rodríguez-Cayetano, Alberto; Jiménez Vivas, Amparo; De Mena Ramos, José Manuel; Alonso García, Gema; Sánchez-Muñoz, Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The main objective of this study was to analyze the acute effect of two teaching models on mood in university students. The sample used is made up of 112 students of the Degree in Physical Activity and Sport Sciences. The Profile of Mood States Questionnaire (Profile of Mood States) by McNair, Lorr and Droppleman (1971) was used in its adaptation to Spanish. Two sessions were conducted, a traditional one based on direct instruction (DI) and an alternative (AL) one based on search and discovery. The traditional model increased all negative factors with significant differences (p£0,05), while the alternative model improved positive mood. By gender, the effect of the teaching model on mood is different, and it does so with significant differences (p£0,05). The alternative model would be the most suitable for improving the positive of student’s mood.